Economic and Social Factors Contributing to CO2 Emission - Paskeh, Mersedeh Khaligh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This research studies the economic and social factors of carbon emissions in the Organization of Petroleum Exporting Countries (OPEC) over period 1995-2014. More especially the thesis studied the link between CO2 emissions and four socio-economic variables (per-capita GDP, urbanization, fossil fuel energy consumption and international trade). A long run relationship is confirmed by Kao (1999), Pedroni (1999) and Johansen (Maddala and Wu, 1999) panel cointegration tests. Fully modified ordinary least squares (FMOLS) outcomes specify the following. The relationship among CO2 emission and GDP is non-linear in OPEC countries, it follows the inverted U-shape suggested by the environmental Kuznets curve hypothesis. Urbanization is responsible for a significant proportion of carbon emissions in OPEC countries. Fossil fuel energy consumption is a significantly positive driver of carbon emission. A large proportion of carbon emissions within OPEC member countries is due to international trade. Keywords: OPEC, Carbon emissions, GDP per-capita, Energy consumption, Urbanization, International trade, FMOLS.

ÖZ: Bu çalışma, 1995-2014 döneminde Petrol İhraç Eden Ülkeler Örgütü'ndeki (OPEC) karbon emisyonlarının ekonomik ve sosyal belirleyicilerini incelemektedir. Bir başka deyişle bu tez karbon emisyonları ile dört sosyo-ekonomik değişken (kişi başına GSYİH, kentleşme, fosil yakıt enerji tüketimi ve uluslararası ticaret) arasındaki denge ilişkisi inceler. Uzun vadeli denge ilişkisi Kao (1999), Pedroni (1999) ve Johansen (Maddala ve Wu, 1999) panel eşbütünleşme testleri ile doğrulanmaktadır. Tamamen değiştirilmiş normal en küçük kareler (FMOLS) sonuçları aşağıdakileri gösterir; Çevresel Kuznets eğrisi hipotezinin önerdiği ters U-şeklini takip eden OPEC ülkelerinde karbon emisyonu ile GSYİH arasındaki ilişki doğrusal değildir. OPEC ülkelerinde karbon salımının önemli bir kısmından şehirleşme sorumludur. Fosil yakıt enerji tüketimi, karbon salınımının önemli bir pozitif etkenidir. OPEC üye ülkelerindeki büyük oranda karbon emisyonu uluslararası ticaretten kaynaklanmaktadır. Anahtar Kelimeler: OPEC, Karbon emisyonları, Kişi başına GSYİH, Enerji tüketimi, Şehirleşme, Uluslararası ticaret, FMOLS.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2019. Supervisor: Assoc. Prof. Dr. Çağay Coşkuner.
Keywords: Economics; Organization of Petroleum Exporting Countries--Petroleum industry and trade; Petroleum products--Energy policy; Petroleum--resource economics; OPEC; Carbon emissions; GDP per-capita; Energy consumption; Urbanization; International trade; FMOLS